Penerapan Teknologi Pengolahan Sampah Melalui Kuliah Kerja Nyata Terpadu Di Desa Kotaraya Tenggara - Rahayu, Ni Wayan Sri Rahayu; I Ketut Suparta; Ni Luh Ayu Eka Damayanti; Melki Sedik Tandea; Ni Nyoman Suwita Ningsih; Ni Luh Sri Nadi; Gede Bagus Wirabuana; Kadek Pande Wijaya; Ni Made Ayu Pastrini; Iwayan Aditya (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2025)
KKNT students are given the opportunity to solve problems in the community. The problem faced by the people of Kotaraya Tenggara Village is about garbage in several places of worship. This causes people who worship uncomfortable. Therefore, waste management technology is proposed to overcome the problems in supporting KKNT students' activities and understanding of the environment. The results showed that students and the community gotong royong to reduce the volume of waste decreased from 80% to 20%, and the community understood about the utilization of technology to reduce the volume of waste. Collaborative activities between students and the community have an impact on environmental awareness of worship, tolerance, and waste processing technology.